Determination of the solubility of methyldopa in supercritical carbon dioxide for drug delivery applications: thermal analysis - Adil Farooq Wali; Sathvik Belagodu Sridhar; Sirajunisa Talath; Jayachithra Ramakrishna Pillai; Javedh Shareef; Mullaicharam Bhupathyraaj; B. K. Manjunatha Goud; Umme Hani (Scientific Reports)
Abstract The production of fine particles by green technology like supercritical carbon dioxide requires the assessment of substantial solubility data at high pressures. This study represents the first determination of the solubility of methyldopa in carbon dioxide at pressures and temperatures ranging from 12 to 30 MPa and from 313.2 to 343.2 K, respectively. The mole fractions were obtained under the aforementioned conditions and ranged from 0.805 × 10⁻5 to 11.345 × 10⁻5. Four empirical models (Chrastil, Bartle et al., Mendez-Santiago, & Teja, and Kumar-Johnston) and two equations of state (Peng-Robinson and Soave-Redlich-Kwong) were used to correlate drug solubility. The K-J model demonstrated the highest accuracy, with an AARD of 8.38% and a R2 value of 0.988. Furthermore, the enthalpy values for the drug in SC-CO₂ were estimated using the Chrastil and Bartle models, resulting in values of 34.35 and 56.87 kJ·mol⁻¹, respectively. The results demonstrate that the SRK more pronounced results than the PR model, with an AARD% of 23.03 and a R2 value of 0.903 compared to 26.42 and 0.837. The article’s conclusions provide a valuable reference for the application of green method in the production of fine particles of methyldopa.